Field-calibrated Hydrologic Engineering Center – River Analysis System modelling of Krueng Keureuto River flow - Y. Bantacut, Alfiansyah; Azmeri, Azmeri; Shaskia, Nina; Amelia, Della; Ziana, Ziana; Rahmatan, Hafnati; Nugroho, Eka O.; Hidayah, Entin (Journal of Water and Land Development, 2026)
Flooding in the Krueng Keureuto Watershed, North Aceh, Indonesia, poses a recurring threat to the community and agricultural productivity. This study aims to develop a reliable hydraulic model using HEC-RAS (Hydrologic Engineering Center – River Analysis System) 6.5 to generate profiles of calibrated water levels and validated flood inundation maps at various return periods. The calibration process used hydrometric data from the Serba Jaman automatic water level recorder (AWLR) to optimise the Manning roughness coefficient. The calibration result showed an optimum Manning value of 0.08 with a simulated depth of 2.55 m and a deviation of only 5.5% from the observed data, indicating that the model is reliable. Unsteady flow simulations showed an increase in flood depth from 7.16 m (Q2) to 10.66 m (Q50), while the inundation area expanded from 379.13 ha to 940.42 ha. Spatial analysis indicated that lowland areas, specifically Tanah Luas and Paya Bakong districts, were most vulnerable, with more than 59% of the inundation area having a depth of more than two meters. These findings emphasise the need for an integrated flood mitigation strategy, combining technical infrastructure with non-structural approaches such as risk- based zoning, early warning systems, and Nature-based Solutions. Methodologically, this study highlights the crucial role of calibration and validation in hydraulic modelling to ensure the accuracy of recommended predictions to strengthen flood risk management in the Krueng Keureuto Watershed and similar watersheds.